DIGITAL LIBRARY UTILIZATION; STRATEGIES TO IMPROVE DIGITAL ISLAMIC LITERACY FOR RELIGION TEACHERS - Nurbayan, Yayan; Sanusi, Anwar; Saleh, Nalahuddin; Khalid, Shofa Musthofa (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
This research is motivated by the condition of the religion teacher. They are expected to be all-knowing about religion, wise, and become a place to ask questions related to religion knowledge among the community. However, several cases and the current findings indicate that not all religion teachers know and master spiritual knowledge. This fanaticism demands that the religion teacher continue to explore inside and have a lot of literature and a personal library. This study aimed to explore increasing the Islamic digital literacy of religion teachers through digital library training strategies and to determine the percentage of spiritual teacher competence in using digital libraries. Therefore, this study uses a mixed method that combines two approaches: qualitative and quantitative. The study results show that training on using digital libraries makes it easier for religion teachers to prepare Islamic references as material for sermons or lectures. In addition, digital libraries can increase Islamic digital literacy activities for religion teachers because. The search for references is more practical, fast, and accurate. After all, it is in the form of an electronic program. This research is expected to be the primary reference for further researchers in improving Islamic digital literacy through digital libraries.